Comparative Analysis of Chemical Components of Purified Essential Oil from Nilam Plants using Gas Chromatography - Emas Agus Prastyo Wibowo; Fadila Mauliani; Utami Nofitasari; Atik Setyani; Nuni Widiarti (The Journal of Pure and Applied Chemistry Research, 2017)
This study aimed to determine the chemical components of the patchouli oil. Patchouli oil is one of the export commodities that have high economic value for Indonesia.  In general, patchouli oil obtained from the hydrodistillation of patchouli leaves. Most industries are still using patchouli oil refiners made by ferrous metal. The rust will dissolve in patchouli oil obtained and led to the resulting of dark oil and patchouli aroma becomes lower. The main purpose of this research is to improve the quality of patchouli oil by the purification process technologies after oil refining process. In this research the purification of the impure and crude oil can be carried out using adsorption process with bentonite. Purification results with UV-VIS spectrophotometer showed that the activation energy at a wavelength of 510 nm-550 nm with 3.9 x 10-19 Joules. GC (Gas Chromatography) analysis showed that there are 13 components from patchouli oil, the 6 dominant peaks were compounds of patchouli alcohol (29.64%), delta-guanine (23.26%), alpha-guanine (21.9%), alpha-patchouline (4.24%), pogostol (4.15%), palustrol (4.00%), beta-pinene (3.9%). Based on the physical properties, the main constituent component content, and the Fe2+ content, refined patchouli oil meets the requirements of the Indonesian National Standards.